Money and Output: A Test of Reverse Causation - Coleman, Wilbur John (American Economic Review, 1996)
This paper attempts to explain the correlation between money and output at various leads and lags with a model in which money is largely neutral and endogenously responds to output. Money is endogenous because both monetary policy and deposit creation are endogenous. Parameters are selected according to the simulated moments estimation technique. While the estimated model succeeds along some dimensions in matching properties of postwar U.S. data, its failure to match key patterns of lead-lag correlations seems to cast doubt on the ability of endogenous money determination, by itself, to quantitatively account for the observed money-output correlations.